2018
DOI: 10.1016/j.ebiom.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Low Bioavailability and High Immunogenicity of a New Brand of E. coli l-Asparaginase with Active Host Contaminating Proteins

Abstract: The drug l-asparaginase is a cornerstone in the treatment of acute lymphoblastic leukemia (ALL). The native E. colil-asparaginase used in Brazil until recently has been manufactured by Medac/Kyowa. Then a decision was taken by the Ministry of Health in 2017 to supply the National Health System with a cheaper alternative l-asparaginase manufactured by Beijing SL Pharmaceutical, called Leuginase®. As opposed to Medac, the asparaginase that has been in use in Brazil under the trade name of Aginasa®, it was not po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 26 publications
4
24
0
1
Order By: Relevance
“…It was the only generic available in the hospital pharmacy at the time of this analysis. The sample was prepared using a method previously described by Zenatti et al Briefly, the sample was reconstituted in normal saline from which 30 μg was aliquoted to which 10 μL urea 8 M and 0.4 μL 250mM Dithiothreitol (DTT) was added. For reduction, the sample was incubated at 56°C for 25 min, following which 0.57 μL 500mM iodoacetamide was added and the sample was incubated for 30 min at room temperature in the dark for alkylation.…”
Section: Methodsmentioning
confidence: 99%
“…It was the only generic available in the hospital pharmacy at the time of this analysis. The sample was prepared using a method previously described by Zenatti et al Briefly, the sample was reconstituted in normal saline from which 30 μg was aliquoted to which 10 μL urea 8 M and 0.4 μL 250mM Dithiothreitol (DTT) was added. For reduction, the sample was incubated at 56°C for 25 min, following which 0.57 μL 500mM iodoacetamide was added and the sample was incubated for 30 min at room temperature in the dark for alkylation.…”
Section: Methodsmentioning
confidence: 99%
“…However, native asparaginase (derived from the bacterium Escherichia coli) has been only intermittently accessible in many settings (82). In 2017, anticipating drug shortage of native asparaginase, the Ministry of Health in Brazil changed the national supplier to a foreign manufacturer that offered a new lowercost generic product (83). Concerned by the lack of published data on this new product, investigators in Brazil studied the drug's properties, and found that it was less bioactive, and contained contaminating proteins that increased the risk for immune-related side effects compared with the native asparaginase used previously (83,84).…”
Section: Access To Essential Medicinesmentioning
confidence: 99%
“…In 2017, anticipating drug shortage of native asparaginase, the Ministry of Health in Brazil changed the national supplier to a foreign manufacturer that offered a new lowercost generic product (83). Concerned by the lack of published data on this new product, investigators in Brazil studied the drug's properties, and found that it was less bioactive, and contained contaminating proteins that increased the risk for immune-related side effects compared with the native asparaginase used previously (83,84). Although the nationwide distribution of this new product in Brazil was halted, this drug continues to be manufactured and distributed to other countries around world (83).…”
Section: Access To Essential Medicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The downstream process must achieve the removal of host cell protein (HCP), process and products related impurities, DNA, buffer, antifoam agents, aggregates, fragments, among others (Jozala et al, 2016; Lopes et al, 2017). Regarding injectable biopharmaceuticals, such as ASNase, the manufacturing process must be even more judicious, since the presence of contaminants, may potentially lead to detrimental clinical consequences (Zenatti et al, 2018).…”
Section: L-asparaginase Manufacturing: Production Process and Purificmentioning
confidence: 99%